Autologous Fibrin Glue With Collagen Carrier During Maxillary Sinus Lift Procedure. Issue 3 (May 2019) - Leighton, Yerko; Weber, Benjamin; Rosas, Eduardo; Pinto, Nelson; Borie, Eduardo
Abstract : Abstract: This study aimed to describe the use of autologous fibrin glue (AFG) with a collagen carrier during maxillary sinus lift procedures with immediate implants during 3 years of follow-up. Twelve patients who had lost their teeth in the region associated to maxillary sinus, with a bone remnant 3 to 5 mm in height, were selected to perform a maxillary sinus augmentation with AFG and collagen membrane, placing the implant immediately. After 5 months, the implants were connected and rehabilitated. The patients were followed-up for a 3-year period, being evaluated every 6 months. At the end of the 3-year follow-up period, 100% implant success was observed, with a mean of bone augmentation of 7.75 mm. Three maxillary sinus membranes were perforated and healed by using AFG and collagen membrane without identify any complication during the follow-up period. Finally, the use of collagen carrier combined with AFG as a filling material during the maxillary sinus lift procedure may be a low-cost and reliable alternative that allows bone formation.